Laboratorijske preiskave za odkrivanje revmatičnih bolezni avtoimunskega izvora - Frlic, Tjaša (Placebo, 2022)
Disorders are part of rheumatic diseases with predominant inflammation and/or autoimmune signs. Autoimmune diseases are very complex and there is not one specific test that can diagnose autoimmune disease conclusively. Testing of mentioned diseases usually starts with basic hematological and biochemical tests. Important tests are hemogram and biochemical test for inflammatory biomarkers, especially sedimentation and C-reactive protein (CRP). With them we can confirm presence of inflammatory process in patient’s body, which is characteristic for reumatic autoimmune diseases. Next test performed is usually test on HEp-2 cells, that is based on indirect immufluorescence. This is a reference method for detection of antinuclear antibodies. Furthermore, enzyme immunochemical methods are mostly used for quantification of specific autoantibodies. Some of them are specific for one disease, but interpretation of test results is by most of them very complicated. During the diagnosis, it is important to consider clinical status of the patient as well.
Keywords: autoantibodies; Avtoimunske bolezni; avtoprotitelesa; complete blood count; ELISA; encimsko-imunokemijske metode; enzyme immunochemical methods; indirect immunofluorescence; indirektna imunofluorescenca; inflammatory markers; krvna slika; Laboratorijske preiskave; označevalci vnetja; Revmatične bolezni